Construction of rigid amine-linked three-dimensional covalent organic frameworks for selectively capturing carbon dioxide. Issue 33 (3rd April 2023) - Zhang, Lin; Wang, Danbo; Cong, Minghao; Jia, Xu; Liu, Zhiguo; He, Lixia; Li, Chaoqin; Zhao, Yingjie
Abstract : A highly rigid amine-linked 3D COF was constructed from two orthogonal building blocks (spirobifluorene and bicarbazole) through a post-synthetic chemical reduction. Abstract : A highly rigid amine-linked 3D COF was constructed from two orthogonal building blocks (spirobifluorene and bicarbazole) through a post-synthetic chemical reduction. The rigid 3D framework decreased the conformational flexibility of the amine linkages, and thus showed a fully preserved crystallinity and porosity. The amine moieties in the 3D COF afforded abundant chemisorptive sites for selectively capturing CO2 .